Numerical study on non-ventilated flame diffusion characteristics in aero-engine nacelle. (28th September 2020) - Zheng, Yu; Cheng, Guanbing; Wang, Guoda; Li, Shuming; Hao, Yimeng
A numerical study on flame diffusion characteristics was effectuated in an aero-engine nacelle. A non-ventilated physical model was established with both ends in open condition. A calculated model was constructed by fire classical software based on LES method. Twelve detectors were placed along horizontal and tangential directions to trace variations of flame characteristic parameters such as temperature, pressure, and velocity together with component concentrations. The results show that the non-premixed flame characteristic parameters undergo both transient and steady states. In the transient state, the temperature, velocity, and oxygen together with soot concentrations evidently change (increase or reduce). Those parameters increase along the inner cylinder in left part of the nacelle, however they vary in opposite manner. Those parameter changes are more evident at the top and bottom of the nacelle. The pressure variation is not evident in the nacelle. In the steady state, those parameter distributions are quasi-symmetrical.